1995
DOI: 10.1136/jmg.32.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Kabuki syndrome-like features in monozygotic twin boys with a pseudodicentric chromosome 13.

Abstract: We present monozygotic twin boys with features of Kabuki syndrome. The twins were discordant for cleft palate and coarctation of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
1
28
0
2
Order By: Relevance
“…12/313 (3.8%) Braun and Schmid [1984]; Halal et al [1989]; Philip et al [1992]; Bay et al [1993]; Lynch et al [1995]; Silengo et al [1996]; Tsukahara et al …”
Section: Acknowledgmentsmentioning
confidence: 97%
“…12/313 (3.8%) Braun and Schmid [1984]; Halal et al [1989]; Philip et al [1992]; Bay et al [1993]; Lynch et al [1995]; Silengo et al [1996]; Tsukahara et al …”
Section: Acknowledgmentsmentioning
confidence: 97%
“…These last 2 findings have been reported at a low frequency in patients with KS [Philip et al, 1992;Ewart-Toland et al, 1998;Wilson, 1998 In addition to hyperinsulinism, the only other previously reported cause of hypoglycemia is isolated ACTH deficiency, but in many other cases of either neonatal or persistent hypoglycemia, the cause remains unknown [Philip et al, 1992;Ewart-Toland et al, 1998;Wilson, 1998;Bereket et al, 2001;Geneviève et al, 2004;Armstrong et al, 2005;Ma et al, 2005]. Diaphragmatic defects have also been rarely reported in KS and include congenital diaphragmatic hernia and unilateral or bilateral eventration of the diaphragm [Lynch et al, 1995;van Haelst et al, 2000;McGaughran et al, 2001;Adam and Hudgins, 2005;Vaux et al, 2005;Abdel-Salam et al, 2008]. The frequency has been estimated to be low (4-8%) but more common than originally suspected, particularly in nonAsian female patients, like the present case [Donadio et al, 2000;Adam and Hudgins, 2005].…”
Section: Discussionmentioning
confidence: 94%
“…Análise cromossômica foi realizada na maioria dos casos publicados com síndrome de Niikawa-Kuroki, e foram descritas algumas alterações envolvendo os cromossomos 4, 6, 9, 10, 12, 13, 15, 17 e os cromossomos sexuais 3,[13][14][15][16][17][18][19][20] . Essas associações, entre síndrome Cabúqui e anomalias cromossômicas variadas -inclusive o presente relato com trissomia 21 -parecem ser acidentais e não, etiologicamente relacionadas.…”
Section: Discussionunclassified